Pengaruh Kombinasi Pupuk Kandang Sapi dan Abu Sabut Kelapa sebagai Pupuk Utama dalam Budidaya Tanaman Brokoli (Brassica oleracia L.) - Eko Binti Lestari (Universitas Muhammadiyah Yogyakarta, 2016)
This research aims to study the effectiveness of coconut fibre ash as an additive nutrient for growth and yield of Broccoli (Brassica oleracia L.), and to determine the best combination between manure and coconut fibre ash in organic farming of Broccoli. This research conducted using single factor experiment that arranged in Randomized Completely Block Design (RCBD). The treatments are (1) Manure 0,75 kg + Coconut fire ash 24,3 g (2) Manure 0,75 kg + Coconut fibre ash12,15 g, (3) Manure 0,75 kg + without Coconut fibre ash, (4) Manure 1 kg + Coconut fibre ash 24,3 g, (5) Manure 1 kg + Coconut fibre ash 12,15 g, (6) Manure 1 kg + without coconut fibre ash, (7) Manure 1,25 kg + Coconut fibre ash 24,3 g, (8) Manure 1,25 kg + Coconut fibre ash 12,15 g, (9) Manure 1,25 kg + without coconut fibre ash. The result showed that the combination between manure and coconut fibre ash have not significantly different in number of leaves, flowering time, fresh weight, flower size, fresh weight of flower. However, the combination between manure 1,25 kg and coconut fibre ash 24,3 g is considered to be the most efficient in organic farming of Broccoli.